Quiet places [videorecording] a look at ecotourism in the Philippines - Gamboa, Joonee
The Philippines is a land of great natural reality. Through the years, many attemps have been made to take advantage of this and develop tourism into one of the country's biggest revenue- earners. With the continuing destruction of the environment and the rapid loss of the very respurces that are being counted upon to draw visitors, it has become necessary to examine what is being done, and determine how the national tourism development program may be revised.